(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Background: Complimentary feeding (CF) practices are quiet frustating in our country. Innaproprite foods in first two years of life have detrimental impact on health and growth of children. The aim of the study was to see the present pattern of CF practices, to identify wrong practices and to develop awareness among medical professionals so that they may encourage appropriate practices more vigorously for reducing child mortality and morbidity. Methods: A cross-sectional study was conducted from October, 2011 to December, 2011 in the Pediatric department (indoor and outdoor) of Sir Salimullah Medical College Mitford Hospital, Dhaka and in a private chamber of a district town of Bangladesh. Four hundred motherchild pairs were selected by non-random convenience sampling method. 6-24 months old children and children under six months (if was on complimentary feeding) were included. Data was collected from the mothers/caregivers of the children in a pretested semi-structured data collection sheet and analyzed by SPSS version 12. Appropriate statistical tests were done. Statistical significance was considered if p value was <0.05. Results: Early initiation was very high (49.25%). Most common first complimentary food was rice gruel with milk (26.56%). Most common current main complimentary food (25.52%) and most common main complimentary food fed in last 24 hours (26.82%) was also rice gruel with milk. Amount of complimentary food per feed was inappropriate in most cases. Frequency of CF was not appropriate in many cases. Fast foods and commercial cereal were given to 54.8% & 33.33% children respectively. Only 1% mothers/caregivers had sound knowledge about CF. Positive support from family regarding practicing appropriate CF was found in 24.75% cases. Feeding practices were mostly influenced by relatives (25%). Conclusion: CF practices are still not ideal in our country. So, all possible interventions should be applied to improve it and thus to improve child survival. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i3.21020